New MOS-C Realization of Transadmittance Type All-Pass Filter Using Modified CBTA - Herencsar, Norbert; Lahiri, Abhirup; Koton, Jaroslav; Sagbas, Mehmet; Ayten, Umut E.; Vrba, Kamil (IEEE, 2011)
This paper reports a new CMOS realization of transadmittance type first-order all-pass filter using an active building block called modified current backward transconductance amplifier (MCBTA). With a simple matching condition, the proposed filter can be created using only one MCBTA, one grounded capacitor, and one grounded resistor, which leads to a compact circuit implementation. The current output available at high-output impedance terminal enables simple cascadibility to subsequent current-mode circuits. Using 0.35 mu m TSMC CMOS technology parameters, SPICE simulation results have validated the workability of the proposed circuit.
Keywords: CONVEYOR; Engineering